Beberapa Permasalah Penerapan Paten dan Upaya untuk Membangun Sistem Paten Indonesia yang Efektif, Wajar, dan Reallstis - Syihabudin Syihab (Fakultas Hukum Universitas Islam Indonesia, 2001)
On August 1, 2001 the government ratified Law No 14 2001 concerning Patent in place of the previous Law. in fact, the reisnothing wrong with Indonesian Patent Law. Unfortunately,the implementation of such law still face various obstacles. The following article will high light problems in implementing patent in Indonesia, and efforts to establish an effective, genuine, and realistic patent system.